2017
DOI: 10.1590/0104-530x2122-16
|View full text |Cite
|
Sign up to set email alerts
|

Campos nos estudos organizacionais: abordagens relacionais?

Abstract: Palavras-chave: Teoria das organizações; Institucionalismo; Poder nas organizações; Dinâmica organizacional.Abstract: This paper analyzes how different approaches of organizational analysis use the notion of 'field'. The philosophical grounds and proposals that motivated the usage of this concept in the social sciences, associated to a specific relational approach illustrated by the sociological approach of Bourdieu, are taken as a reference. Identifying the genesis and paying particular attention to the confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
0
5
0
7
Order By: Relevance
“…Concerning human resources, the maintenance of an appropriate nursing staff size has been appointed as a challenge not only for Surgical Centers (14) . Exemplifying difficulties related to human resources in all of the healthcare network, a study conducted in Rio Grande do Sul state with nursing professionals from primary and tertiary attention has found that lack of physical structure and equipment and an excessive number of patients per professional are risk factors for the occurrence of moral suffering among nurses (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning human resources, the maintenance of an appropriate nursing staff size has been appointed as a challenge not only for Surgical Centers (14) . Exemplifying difficulties related to human resources in all of the healthcare network, a study conducted in Rio Grande do Sul state with nursing professionals from primary and tertiary attention has found that lack of physical structure and equipment and an excessive number of patients per professional are risk factors for the occurrence of moral suffering among nurses (15) .…”
Section: Discussionmentioning
confidence: 99%
“…There is a notion of field used by the authors as an analytical category that makes it possible to understand how institutions act in the dynamics of actors and, consequently, how they corroborate the maintenance of the status quo. This is the perspective adopted on this research as it was for Fligstein and McAdam (2012): it gathers, in a single thesis, the discussions on origin, maintenance and transformation of a field, through the investigation of the dynamics of stability and change in its interior (CANDIDO et al, 2018).…”
Section: Theoretical Approach Used For Data Analysismentioning
confidence: 99%
“…Field theories have been increasingly influential in organization studies as they represent an alternative to both rational individualist and functionalist perspectives (Martin, 2003;Candido et al, 2018). While the approach is in line with the interpretative paradigm of the study of organizations, which claims that the social sciences deal with phenomena that are subjective and open to interpretation (Morgan, 2005), it recognizes, in line with Durkheim (2002) idea of social fact, that widely shared interpretations about certain aspects may get "naturalized" in the multiple instances of social life, becoming objectified.…”
Section: The Strategic Action Fields and Social Skillsmentioning
confidence: 99%
“…The definition of these shared references that enable collective action entails power relations. While in specific field theories, power relations are viewed in a negative vein, the strategic action field approach emphasizes the positive character of power as a facilitator of cooperation (Candido et al, 2018). In this sense, fields can be defined as "a social arena, where something is at stake and actors come to engage in social action with other actors under a set of common understandings and with a set of resources that help define the social positions in the field" (Fligstein, 2013, p.41).…”
Section: The Strategic Action Fields and Social Skillsmentioning
confidence: 99%